Hydrolysis of GTP by Sec4 protein plays an important role in vesicular transport and is stimulated by a GTPase-activating protein in Saccharomyces cerevisiae. - Walworth, N C (1992)
Sec4, a GTP-binding protein of the ras superfamily, is required for exocytosis in the budding yeast Saccharomyces cerevisiae. To test the role of GTP hydrolysis in Sec4 function, we constructed a mutation, Q-79----L, analogous to the oncogenic mutation of Q-61----L in Ras, in a region of Sec4 predicted to interact with the phosphoryl group of GTP. The sec4-leu79 mutation lowers the intrinsic hydrolysis rate to unmeasurable levels. A component of a yeast lysate specifically stimulates the hydrolysis of GTP by Sec4, while the rate of hydrolysis of GTP by Sec4-Leu79 can be stimulated by this GAP activity to only 30% of the stimulated hydrolysis rate of the wild-type protein. The decreased rate of hydrolysis results in the accumulation of the Sec4-Leu79 protein in its GTP-bound form in an overproducing yeast strain. The sec4-leu79 allele can function as the sole copy of sec4 in yeast cells. However, it causes recessive, cold-sensitive growth, a slowing of invertase secretion, and accumulation of secretory vesicles and displays synthetic lethality with a subset of other secretory mutants, indicative of a partial loss of Sec4 function. While the level of Ras function reflects the absolute level of GTP-bound protein, our results suggest that the ability of Sec4 to cycle between its GTP and GDP bound forms is important for its function in vesicular transport, supporting a mechanism for Sec4 function which is distinct from that of the Ras protein.